2015
DOI: 10.1371/journal.pone.0127022
|View full text |Cite
|
Sign up to set email alerts
|

Serum N-Glycans: A New Diagnostic Biomarker for Light Chain Multiple Myeloma

Abstract: The aim of this study was to evaluate the diagnostic and differential diagnostic power of serum N-glycans for light chain multiple myeloma (LCMM). A total of 167 cases of subjects, including 42 LCMM, 42 IgG myeloma, 41 IgA myeloma, and 42 healthy controls were recruited in this study. DNA sequencer-assisted fluorophore-assisted capillary electrophoresis (DSA-FACE) was applied to determine the quantitive abundance of serum N-glycans. The core fucosylated, bisecting and sialylated modifications were analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…confirmed that reduced homing and engraftment of ST3GAL6 sialyltransferase knockdown in MM cells in the bone marrow decreased tumor propagation . Decreased core fucosylation, appearance of bisecting forms and increased sialylation of serum glycoproteins were observed in patients with light‐chain multiple myeloma (LCMM) . Also in MM, recently low galactosylation and fucosylation was found .…”
Section: Introductionmentioning
confidence: 68%
“…confirmed that reduced homing and engraftment of ST3GAL6 sialyltransferase knockdown in MM cells in the bone marrow decreased tumor propagation . Decreased core fucosylation, appearance of bisecting forms and increased sialylation of serum glycoproteins were observed in patients with light‐chain multiple myeloma (LCMM) . Also in MM, recently low galactosylation and fucosylation was found .…”
Section: Introductionmentioning
confidence: 68%
“…However, the DSA‐FACE method remains an effective glycomic approach for the discovery of cancer biomarkers. Differential biomarkers of clinical application potential can be identified with simple structural information using this method with higher repeatability and better quality control than the original method, as previously reported . Aberrant sialylation has been implicated in several cancers .…”
Section: Discussionmentioning
confidence: 65%
“…However, most of these approaches involve chromatographic separation, mass spectrometry analysis or various microarrays, along with high complexity and low cost‐efficiency . Herein, we employ a modified DNA sequencer‐assisted fluorophore‐assisted capillary electrophoresis (DSA‐FACE) technology, which is originally established by Callewaert and coworkers to decipher the global N ‐glycome of serum . Discovery of differentially expressed glycans from whole serum may serve to present candidate biomarkers for the discrimination of ECCA.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of modifying N -glycan samples prior to CE separations using enzymes was recognized early. 90 Applications with CE have been performed off-line with a variety of enzymes 28 , 59 , 88 , 91 and typically focus on removal of sialic acids 52 , 66 , 92 in some cases as a means to reduce complexity of the CE separation. 92 These reactions are typically performed overnight at an elevated temperature and a specified pH.…”
Section: Methods To Identify Glycansmentioning
confidence: 99%